ORGANIZATIONAL AND ECONOMIC FUNDAMENTALS OF IMPROVEMENT OF ORGANIZATIONAL STRUCTURES OF BUSINESS ORGANIZATIONS - SHERSHNOVA, ZOIA; HISEM, SVITLANA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article considers the need of transformations in the management systems of business organizations in modern conditions, which can be described as crisis - forming, as they are formed under the influence of a pandemic. The dynamic environment requires changes in the operation of business organizations due to different changes not only in demand in certain sectors of the economy and social groups (based on declining incomes), but also the impact of inflation in general, energy dependence on foreign sources and individuals, environmental factors, etc. To overcome the crisis, the operation of business organizations that need to change must be managed for their next usage in influencing on certain business elements. This means that the management system of a business organization must be adapted to changing conditions. The most inertial element of the management system of a business organization is the organizational structure of management (OSM). Management systems of business organizations, and especially their OSM, in most Ukrainian organizations do not correspond to their needs. Organizations that were established 30 or more years ago (in Soviet times) have, as a rule, management systems that are more or less correspond to the conditions of a stable environment of the USSR. Newly created business organizations, as research shows, form management systems without taking into consideration the modern theory of organizational development and organizational design practice (which is confirmed by the experience and efficiency of successful enterprises). Detailed analysis and diagnosis of the business organizations should be a prerequisite for their effective transformations. In the activities of Ukrainian business organizations we can observe more or less developed financial analysis based on standardized financial statements. However, it`s still hard to determine the real state of business organizations, because there was a loss of vital areas of economic analysis (use of fixed assets, stocks of various types, economic evaluation of resource markets, pricing options under the influence of individual factors, costs of core and ancillary activities, etc.). There is almost no organizational analysis (OA) and diagnostics as a basis for improving the management system as a whole and OSM as an integral part of it. It is known that the management system is a tool of controlled economic operation. The composition of the management system requires a combination of economic and organizational analysis: the managed system focuses on the evaluation of results on economic analysis, and the manager - on organizational analysis. To determine the synergistic effects of the system, it is necessary to combine these two components, which will serve as a basis for developing strategies for sustainable development of business organizations.
Keywords: business organization; economic analysis; organizational analysis; diagnostic analysis; managed development; synergy effect